Diagnostic Performance of Glymphatic System Evaluation Using Diffusion Tensor Imaging in Idiopathic Normal Pressure Hydrocephalus and Mimickers. (20th June 2019) - Yokota, Hajime; Vijayasarathi, Arvind; Cekic, Milos; Hirata, Yoko; Linetsky, Michael; Ho, Michael; Kim, Won; Salamon, Noriko
Abstract : Purpose . To investigate the pathological change of the glymphatic system in idiopathic normal pressure hydrocephalus (iNPH) using diffusion tensor imaging (DTI) analysis. Materials and Methods . 24 right-handed patients were referred to our hydrocephalus clinic for assessment of ventriculomegaly and gait impairment. 12 of 24 were diagnosed as pseudo-iNPH (piNPH) based on assessment by a neurologist. Diffusivity maps in the direction of the x-axis (right-to-left) (Dx), y-axis (anterior-to-posterior) (Dy), and z-axis (inferior-to-superior) (Dz) were computed. The diffusion map was coregistered to International Consortium for Brain Mapping (ICBM) DTI-81 atlas. The analysis along the perivascular space (ALPS) index was defined as mean (Dxpro, Dypro)/mean (Dypro, Dzasc), where Dxpro and Dxasc are Dx values in the projection and association fiber areas, respectively. Evans index and callosal angle were also assessed on each case. Results . ALPS indexes of the control, piNPH, and iNPH cases were 1.18 ± 0.08, 1.08 ± 0.03, and 0.94 ± 0.06, respectively, and there were significant differences among the groups (control vs. piNPH, P = 0.003; control vs. iNPH P < 0.001; piNPH vs. iNPH, P < 0.001). Area under curve (AUC) was 0.92, 1.00, and 1.00 on control vs. piNPH, control vs. iNPH, and piNPH vs. iNPH on ROC analysis. Between piNPH and NPH, ALPS index has higher diagnostic performance than Evans index and callosal angle (AUC = 1.00 vs. 0.84, P = 0.028; AUC = 1.00 vs. 0.74, P = 0.016). Conclusion . Atlas-based ALPS index using the DTI method differentiated among iNPH, piNPH, and controls clearly.